The Integration of Business Ethics Principles into Corporate Governance and Director Liability: A Turkish Legal Perspective (European Journal of Marketing and Economics, 2026)
This study explores the foundational relationship between business ethics principles and their practical integration into corporate governance frameworks, particularly examining the implications for director liability. Initially, the paper defines business ethics and elucidates its core principles, including integrity, fairness, trust, openness, and truthfulness. Subsequently, it analyzes various facets of business ethics, with a specific focus on its legal ramifications and the extent to which these ethical considerations have been codified into law. The study posits that business ethics significantly influences business law and corporate governance, becoming "legalized" through corporate codes of conduct. A central aim is to clarify the explicit mention of business ethics within Turkish law, particularly in the Code of Corporate Governance pertaining to public companies, and to discuss the legal impact of this regulation. This legal inclusion raises critical questions, notably whether ethical standards can serve as a direct source of liability for boards and directors. The paper then examines the intricate interrelation between ethical standards, corporate governance codes, and director liability. It concludes by illustrating how business ethics acts as a foundational concept, informing fields such as corporate governance, corporate social responsibility, director liability, and human rights in business (especially concerning employee working conditions), demonstrating its significant intersection with all these areas. Finally, the study clarifies the specific adoption of business ethics into the Turkish legal system and its impact on business practices.
Keywords: Business Ethics, Corporate Governance, Director Liability, Ethical Principles, Turkish Law, Corporate Social Responsibility, Legal Integration